Spanish Spaces Landscape, Space and Place in Contemporary Spanish Culture - Davies, Ann (Contemporary Hispanic and Lusophone Cultures, 2012)
Spanish Spaces is a pioneering study that marries contemporary cultural geography with contemporary Spanish culture. The field of cultural geography has grown both extensively and rapidly, as has the field of cultural analysis and debate on Spanish cultural texts; yet despite a convergence in study between cultural geography (and cultural studies more widely) and cultural texts themselves, this has made little impact to date within the area of contemporary Spanish cultural studies. Drawing on case studies from contemporary Spanish film and literature, Davies explores the themes of memory and forgetting, nationalism and terrorism, crime and detection, gender, tourism and immigration, investigating what it means to think of space and places in specifically Spanish terms.